2021
DOI: 10.4995/muse.2021.15492
|View full text |Cite
|
Sign up to set email alerts
|

Activity Preferences of Generation Z Students for Tertiary Physical Education: Implications for Curriculum Enhancement

Abstract: <p>This research aimed to look into Generation Z Students' preferred activities to enhance the curriculum content of Tertiary Physical Education in one of the leading Universities in the Philippines using the phenomenological research design due to the fact that a great number of students in Physical Education have dropped out. A total of 110 research participants were involved in focus group discussions, in-depth interviews, and extensive field observation.  Results from focus group discussions, intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25]. Therefore, this indicates why teacher variables, in along with the activities they select and present to students, play a key role in generating students' interest and strengthening engagement in the efficient formation of physical culture.…”
supporting
confidence: 79%
“…Consistent with the available data, we can speculate that teachers can influence their students' views forward into Physical Education, which in turn can reduce students' interest and engagement in school [20,21,22]. Multiple studies have demonstrated that students' perspectives might be influenced by the variety of physical and sporting activities they are exposed to in school [23,24,25]. Therefore, this indicates why teacher variables, in along with the activities they select and present to students, play a key role in generating students' interest and strengthening engagement in the efficient formation of physical culture.…”
supporting
confidence: 79%
“…In line with the evidence presented previously, it is possible to postulate that teachers may also affect students' attitudes toward Physical Education, which may lead to a decrease in individual interest and engagement in school [20][21][22]. Other research, have also found that the physical and sporting activities that are presented to students are associated with and can alter students' attitudes [23][24][25]. Therefore, this explains why teacher variables, in addition to the activities they choose and offer to students, play a crucial role in establishing students' interest and strengthening involvement in the successful development of physical culture.…”
Section: Introduction Physical Culture On Campussupporting
confidence: 71%
“…In line with the aforementioned findings, studies have confirmed that teacher factors may also affect student attitudes toward Physical Education (González-Peño, Franco and Coterón, 2021;Malinauskas, Emeljanovas and Valantine, 2018;Scrabis-Fletcher and Silvermanv, 2010). Additionally, physical and sports activities were also identified as predictors of students' attitudes (Lobo, Dimalanta and Bautista, 2022;Sağın, 2022;Tagare and Villaluz, 2021). Hence, it can be concluded that physical education teachers are the people behind solidifying students' interest and engagement in the subject through carefully selected activities promoting physical culture.…”
Section: Promoting Physical Culture Inside the Campussupporting
confidence: 59%